Tong Komposter Rumah Tangga sebagai Upaya Pengelolaan Sampah Berkelanjutan di Desa Luthu Lamweu Kecamatan Sukamakmur Aceh Besar - Ibrahim, Tilaili; Nurjannah, Nurjannah; Sofyana, Sofyana (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2024)
Barrel composting offers an efficient and sustainable solution for organic waste management in community settings particularly at the household level. Waste management is also a problem in rural areas including the village of Luthi Lamweu, District of Sukamakmir, Aceh Besar. This program aimed to educate and produce about barrel composting using organic household waste by engaging women. By converting household organic waste into nutrient-rich compost, barrel composting helps reduce landfill waste while improving soil health for local agriculture. Women's participation played a crucial role in the success of this initiative, as they learned about composting techniques and the value of waste recycling. The project not only promoted environmental awareness but also encouraged local ownership of sustainable practices. The findings demonstrate that barrel composting can serve as a practical, scalable solution for organic waste management, contributing to both environmental conservation and community empowerment.